On the Effect of Atoms in Solid Solution on Grain Growth Kinetics - Hersent, Emmanuel; Marthinsen, Knut; Nes, Erik (Metallurgical and materials transactions. A, Physical metallurgy and materials science, 2014)
The discrepancy between the classical grain growth law in high purity metals (grain size D ∝ t 1 / 2 ) and experimental measurements has long been a subject of debate. It is generally believed that a time growth exponent less than 1/2 is due to small amounts of impurity atoms in solid solution even in high purity metals. The present authors have recently developed a new approach to solute drag based on solute pinning of grain boundaries, which turns out to be mathematically simpler than the classic theory for solute drag. This new approach has been combined with a simple parametric law for the growth of the mean grain size to simulate the growth kinetics in dilute solid solution metals. Experimental grain growth curves in the cases of aluminum, iron, and lead containing small amounts of impurities have been well accounted for.